ANTHIAS HUTOMOI, A NEW SPECIES OF SERRANID FISH FROM INDONESIA (PERCIFORMES, SERRANIDAE) - Allen, Gerald A.; Burhanuddin, - (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1976)
Anthias hutomoi, a member of the family Serranidae (subfamily Anthiinae) is described from 11 specimens taken by trawl at Seram, Indonesia. It appears to be allied to Anthias cichlops (BLEEKER,), but differs in several important respects, including head length, caudal shape, and counts for the lateral-line, soft dorsal rays, and pectoral rays.